2015
DOI: 10.1371/journal.pone.0120497
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens Alpha-Toxin Induces Gm1a Clustering and Trka Phosphorylation in the Host Cell Membrane

Abstract: Clostridium perfringens alpha-toxin elicits various immune responses such as the release of cytokines, chemokines, and superoxide via the GM1a/TrkA complex. Alpha-toxin possesses phospholipase C (PLC) hydrolytic activity that contributes to signal transduction in the pathogenesis of gas gangrene. Little is known about the relationship between lipid metabolism and TrkA activation by alpha-toxin. Using live-cell fluorescence microscopy, we monitored transbilayer movement of diacylglycerol (DAG) with the yellow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…In contrast, U73343 did not block the toxin-induced responses. To determine DAG formation in the cytoplasmic membrane of MDCK cells, we utilized an indicator, enhanced yellow fluorescent protein (EYFP)-tagged C1A and C1B regions of protein kinase C-γ (EYFP-C1AB), which permits the binding of DAG [39]. The transfection of MDCK cells with EYFP-C1AB resulted in homogeneous fluorescence signals throughout the cells ( Figure 2E).…”
Section: Epsilon-toxin Activates Phospholipase Cγ-1 In Mdck Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, U73343 did not block the toxin-induced responses. To determine DAG formation in the cytoplasmic membrane of MDCK cells, we utilized an indicator, enhanced yellow fluorescent protein (EYFP)-tagged C1A and C1B regions of protein kinase C-γ (EYFP-C1AB), which permits the binding of DAG [39]. The transfection of MDCK cells with EYFP-C1AB resulted in homogeneous fluorescence signals throughout the cells ( Figure 2E).…”
Section: Epsilon-toxin Activates Phospholipase Cγ-1 In Mdck Cellsmentioning
confidence: 99%
“…Plasmid for the enhanced yellow fluorescent protein-fused C1AB domain of protein kinase C-γ (EYFP-C1AB) was constructed [39]. For DG staining on the outer leaflet of the plasma membrane, the plasmid was electroporated into MDCK cells utilizing a Neon Transfection System (ThermoFisher).…”
Section: Confocal Imaging Of Diacylglycerolmentioning
confidence: 99%
“…perfringens alpha-toxin induces the respiratory burst in neutrophils by inducing the activation of PKC via two separate pathways: elevation of DAG generated by activation of an endogenous PLC through a pertussis toxin-sensitive GTP-binding protein, and activation of a tropomyosin-related kinase receptor (TrkA receptor) that leads to PDK1 phosphorylation (225,226). In epithelial cells, alpha-toxin binding to GM1a ganglioside induces TNF-␣ and IL-8 production through the activation of the TrkA receptor and the p38 mitogen-activated protein kinase (MAPK) pathway, as well as a PLC-␥1, ERK1/2-NF-B-dependent pathway (232)(233)(234). TNF-␣ plays an important role in the toxic effect of alpha-toxin, since the administration of specific antibodies against TNF-␣ protects mice from its lethal effect (235).…”
Section: Fig 11mentioning
confidence: 99%
“…Ichikawa et al [ 33 ] reported that GM1 clustering promotes the enrichment of TrkA in the lipid raft and activation of downstream signal transduction pathways. We also found that alpha-toxin induced diacylglycerol formation at the plasma membrane [ 34 ]. The ensuing flip-flop motion of diacylglycerol influences membrane dynamics, thereby promoting GM1a clustering and activation of endogenous phospholipase C-γ1 via TrkA [ 34 , 35 ].…”
Section: Relationship Between Alpha-toxin and Gangliosidesmentioning
confidence: 99%
“…We also found that alpha-toxin induced diacylglycerol formation at the plasma membrane [ 34 ]. The ensuing flip-flop motion of diacylglycerol influences membrane dynamics, thereby promoting GM1a clustering and activation of endogenous phospholipase C-γ1 via TrkA [ 34 , 35 ]. These results suggest that the binding of alpha-toxin to GM1a plays an important role in the clustering and activation of TrkA ( Figure 2 ).…”
Section: Relationship Between Alpha-toxin and Gangliosidesmentioning
confidence: 99%